Osteointegration in Compliant Self-Adjusting Compression Fixation Shown by Backscatter Electron Microscopy: A Case Report. Issue 3 (October 2019) - Christ, Alexander B.; Baral, Elexis; Wright, Timothy M.; Healey, John H.
Compliant self-adjusting compression implants are a novel approach to increase the durability of megaprosthesis fixation. However, there is no report of current implant designs that documents the bone-prosthetic interface of this implant. A well-fixed compliant, self-adjusting distal femoral replacement was retrieved from a patient undergoing revision unrelated to fixation. The prosthesis-bone interface was preserved, embedded in poly(methyl methacrylate), and sectioned into 2–4-mm slices. Slices were then imaged using backscatter electron microscopy, and ongrowth and ingrowth were quantified using imaging software. The average percentage of bony ongrowth from five successive sections was 52.5%, and the average percentage of ingrowth into the porous titanium surface was 13.5%. We found that bone ongrowth on the cortex between anchor plug and spindle averages more than 50% and up to 70% depending upon the slice examined with backscatter electron microscopy. Bone ingrowth was consistently around 13% on every slice examined. This is a new finding compared with prior spindle designs, likely due to the addition of hydroxyapatite-coated porous metal titanium surface on the spindle. This report is an important step in understanding the mechanism of bony fixation generated by this implant and supports its increased use in oncological and complex reconstructive situations.